A first-principles study of the electronic structure and mechanical and optical properties of CaAlSiN3. Issue 22 (14th June 2015) - Wang, Zhanyu; Shen, Bo; Dong, Fei; Wang, Songyou; Su, Wan-Sheng
<x xml:space="preserve">Abstract</x> A systematic study of the basic characteristics of CaAlSiN3.